Sam68 mediates leptin signaling and action in human granulosa cells: possible role in leptin resistance in PCOS - Vilariño-García, Teresa (Endocr Connect, 2020)
INTRODUCTION: Polycystic ovary syndrome (PCOS) is a complex metabolic disorder associated with ovulatory dysfunction, hyperandrogenism, obesity, and insulin resistance, that leads to subfertility. Sam68 is an RNA-binding protein with signaling functions that is ubiquitously expressed, including gonads. Sam68 is recruited to leptin signaling, mediating different leptin actions. OBJECTIVE: We aimed to investigate the role of Sam68 in leptin signaling, mediating the effect on aromatase expression in granulosa cells and the posible implication of Sam68 in the leptin resistance in PCOS. MATERIALS AND METHODS: Granulosa cells were from healthy donors (n = 25) and women with PCOS (n = 25), within the age range of 20 to 40 years, from Valencian Infertility Institute (IVI), Seville, Spain. Sam68 expression was inhibited by siRNA method and overexpressed by expression vector. Expression level was analysed by qPCR and immunoblot. Statistical significance was assessed by ANOVA followed by different post-hoc tests. A P value of <0.05 was considered statistically significant. RESULTS: We have found that leptin stimulation increases phosphorylation and expression level of Sam68 and aromatase in granulosa cells from normal donors. Downregulation of Sam68 expression resulted in a lower activation of MAPK and PI3K pathways in response to leptin, whereas overexpression of Sam68 increased leptin stimulation of signaling, enhancing aromatase expression. Granulosa cells from women with PCOS presented lower expression of Sam68 and were resistant to the leptin effect on aromatase expression. CONCLUSIONS: These results suggest the participation of Sam68 in leptin receptor signaling, mediating the leptin effect on aromatase expression in granulosa cells, and point to a new target in leptin resistance in PCOS.